Infective Endocarditis in Ireland: A Nationwide Analysis - Aoife Maher; Eoghan de Barra; Fidelma Fitzpatrick; Fiona Boland; James O’Connell; Brendan McAdam (Journal of Clinical Medicine, 2026)
Introduction: Infective endocarditis (IE) remains a serious life-threatening condition associated with substantial morbidity and mortality. Within the Republic of Ireland, there is limited national data regarding the clinical and economic impact of IE. This study aimed to describe IE in Ireland. Methods: We conducted a retrospective cohort study using national Hospital Inpatient Enquiry (HIPE) data accessed through the National Quality Assurance and Improvement System (NQAIS). All admissions with a principal diagnosis of acute or subacute infective endocarditis (ICD10: I33.0, I33.8) from 1 January 2018–30 July 2025 were included. Duplicate episodes, incomplete records, nonemergency admissions, and cases without documented transoesophageal echocardiography (TOE) were excluded. Demographic, clinical, procedural, and outcome variables were explored. Costs were assigned using Healthcare Pricing Office guidance for length of stay (LOS). Results: A total of 441 patients met inclusion criteria. The mean age was 64.1 years (SD 17.0), and 75.5% were male. Surgical intervention occurred in 18.4% of cases. Surgically managed patients were younger than medically managed patients (mean age 58.8 years vs. 65.7 years, p < 0.001) and experienced a longer LOS (mean of 51 days vs. 36 days, p < 0.001). The overall in-hospital mortality rate was 9.5% (n = 42). On multivariable analysis, higher comorbidity burden (measured by Charlson comorbidity index (CCI)) was independently associated with in-hospital mortality (OR 1.09, 95% CI 1.06–1.13, p < 0.001). The total expenditure was €20.6 million. Discussion: IE in Ireland affects predominantly older, comorbid patients and is associated with significant healthcare resource utilization. In-hospital mortality rates appear favourable compared with published international series.